Respuesta :

 [tex]0.2(x + 1) + 0.5x = -0.3(x - 4)[/tex] 

[tex]0.2x+0.2+0.5x=-0.3x+1.2 [/tex] 

[tex]0.7x+0.2=-0.3x+1.2[/tex] 

[tex]0.7x=-0.3x+1.2-0.2[/tex] 

[tex]0.7x=-0.3x+1[/tex] 

[tex]0.7x+0.3x=1[/tex] 

[tex]x=1[/tex]

Answer:  The required value of x is 1.

Step-by-step explanation:  We are given to solve the value of x in the following equation :

[tex]0.2(x+1)+0.5x=-0.3(x-4)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

To find the value of x in the above equation, we must solve the equation (i) as follows :

[tex]0.2(x+1)+0.5x=-0.3(x-4)\\\\\Rightarrow 0.2x+0.2+0.5x=-0.3x+1.2\\\\\Rightarrow 0.7x+0.2=-0.3x+1.2\\\\\Rightarrow 0.7x+0.3x=1.2-0.2\\\\\Rightarrow x=1.[/tex]

Thus, the required value of x is 1.

ACCESS MORE